2015
DOI: 10.1039/c4cc09956g
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance nanoporous Si/Al2O3 foam lithium-ion battery anode fabricated by selective chemical etching of the Al–Si alloy and subsequent thermal oxidation

Abstract: Nanostructured micrometer-sized Al-Si particles are synthesized via a facile selective etching process of Al-Si alloy powder. Subsequent thin Al2O3 layers are introduced on the Si foam surface via a selective thermal wet oxidation process of etched Al-Si particles. The resulting Si/Al2O3 foam anodes exhibit outstanding cycling stability (a capacity retention of 78% after 300 cycles at the C/5 rate) and excellent rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…As Figure illustrates, when the C rate is returned step by step from 12 C to C/4 again, the original capacity is largely recovered in each level, revealing the robustness and stability of our structure. These results are comparable to or even better than some of previously reported Si/Al 2 O 3 composite LIB anodes …”
Section: Resultssupporting
confidence: 89%
“…As Figure illustrates, when the C rate is returned step by step from 12 C to C/4 again, the original capacity is largely recovered in each level, revealing the robustness and stability of our structure. These results are comparable to or even better than some of previously reported Si/Al 2 O 3 composite LIB anodes …”
Section: Resultssupporting
confidence: 89%
“…It is well known that beside the binder, porous Si particles are intriguing structures including large free spaces for expansion during lithiation process to improve their cycling performance. Therefore, we decided to prepare the 3D porous Si particles as anodes through a simple acid etching of Al from Al‐Si alloy powders . X‐ray diffraction (XRD) patterns clearly demonstrated that the acid etching of Al‐Si alloy particles produced pure crystalline Si particles with the absence of Al peaks after etching ( Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Distinctive microstructures from the eutectic phase results in alloy products with mesopores after selective etching . As shown in the left column of Figure a, Al−Si alloys, which are comprised of 87.4 wt% Al and 12.6 wt% Si (i. e., the eutectic point in the Al−Si binary phase diagram), result in a sponge‐like structure without significant deformation either in morphology or crystallinity, even after over 80 wt% of Al is removed from the alloy . Similarly, a Si/SiO 2 composite prepared from a disproportionation of SiO microparticles will have a porous Si structure after selective SiO 2 etching by HF treatment (right column of Figure a) .…”
Section: Preparation Of Nanostructured Simentioning
confidence: 99%
“… Schematic illustrations for etching methods of nanostructured Si. (a) Al−Si eutectic and disproportionation of SiO . (b) Bulk Si by the metal‐assisted chemical etching (MACE) method.…”
Section: Preparation Of Nanostructured Simentioning
confidence: 99%